Flood Aftermath on Soil Quality in North Central Laterites of Kerala - Riaj Rahaman (Journal of the Indian Society of Soil Science, 2022)
Soil quality mostly refers to the dynamic properties of surface soil (0 to 25 cm) that can be strongly altered by management practices. The study aimed at the assessment of soil quality in the post-flood soils and the findings were quantified by expressing as a function of measurable soil properties. Among the 23 parameters analyzed on 100 geo-referenced soil samples, soil pH, bulk density, available nitrogen (N), phosphorus (P), calcium (Ca), copper (Cu), boron (B) and microbial biomass carbon (MBC) were found as key indicators influencing soil quality. Depending on the contribution of indicators to soil quality they were categorised, scored and finally, weighted indicators were summarised into soil quality index (SQI) using standard formula. The contribution of pH and bulk density was highest to soil quality index while, the lowest contribution was shared by available B. The SQI was highest in Pariyaram Panchayat, where the analytical value of key indicators were near to optimum range and lowest in Meloor due to the poor content of available N and MBC. The deviation in soil quality was measured and expressed in terms of relative soil quality index (RSQI), which was found to be medium in 82% of the samples. Improvement in SQI can be achieved by optimizing the key soil indicators in each site.